1999
DOI: 10.1038/sj.onc.1202967
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the fork head domain transcription factor MPP2 with the human papilloma virus 16 E7 protein: enhancement of transformation and transactivation

Abstract: The high risk human papillomavirus (HPV) type 16 E7 protein a ects cell growth control and promotes transformation by interfering with functions of cellular proteins. A key target of E7 is the tumor suppressor protein p105RB. Although this interaction is required for E7-dependent transformation, other cellular molecules must also be involved, because some E7 mutants that have reduced transforming abilities still bind to p105RB. In order to identify additional proteins that interact with E7 and that may be resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(84 citation statements)
references
References 74 publications
0
84
0
Order By: Relevance
“…Interestingly, when the same experiments were done with the E7 LXCXE mutant, less cooperativity was seen indicating that the LXCXE motif may have a role in E7 cooperation with B-Myb and FoxM1 and the B-Myb-MuvB complex (Supplementary Figure S1A and S1B). HPV16 E7 interacts with B-MyB and FoxM1 and is recruited to mitotic promoters The synergistic increase of mitotic genes transcript levels by HPV16 E7 and B-Myb or FoxM1 strongly suggested that E7 directly interacts with B-Myb or FoxM1, as demonstrated previously for FoxM1 only, 9 and could perhaps form transcriptional complexes with these proteins. We, therefore, looked for E7:B-Myb interaction by performing immunoprecipitation in extracts of 293T cells that overexpressed E7 and B-Myb and were indeed able to detect an interaction between these two proteins (Figure 3a).…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…Interestingly, when the same experiments were done with the E7 LXCXE mutant, less cooperativity was seen indicating that the LXCXE motif may have a role in E7 cooperation with B-Myb and FoxM1 and the B-Myb-MuvB complex (Supplementary Figure S1A and S1B). HPV16 E7 interacts with B-MyB and FoxM1 and is recruited to mitotic promoters The synergistic increase of mitotic genes transcript levels by HPV16 E7 and B-Myb or FoxM1 strongly suggested that E7 directly interacts with B-Myb or FoxM1, as demonstrated previously for FoxM1 only, 9 and could perhaps form transcriptional complexes with these proteins. We, therefore, looked for E7:B-Myb interaction by performing immunoprecipitation in extracts of 293T cells that overexpressed E7 and B-Myb and were indeed able to detect an interaction between these two proteins (Figure 3a).…”
Section: Resultsmentioning
confidence: 59%
“…7 The HPV16 E7 protein had previously been shown to specifically activate B-Myb transcription 8 and to interact with and activate FoxM1. 9 Mammalian B-Myb is a product of the MYBL2 gene that is expressed in all dividing cells, such that loss of function mutations in this gene causes early embryonic lethality. 10 Orthologous MYBL2 in both drosophila [11][12][13] and zebra fish 14 is similarly essential for the regulation of mitotic progression.…”
Section: Introductionmentioning
confidence: 99%
“…Coimmunoprecipitated proteins were detected by Western blot analysis. PARP-10 expression was analysed by Western blotting using whole-cell extracts prepared in RIPA buffer (Luscher-Firzlaff et al, 1999). For immunoprecipitations and Western blot analysis, anti-HA-tag mAb 3F10 (Roche) and anti-Flag-tag mAb M2 (Sigma) were used.…”
Section: Protein Analyses Antibodies and In Vitro Transcription And mentioning
confidence: 99%
“…The supplements were 100 U of penicillin, 100 mg/ml streptomycin, and 10% fetal calf serum (FCS). Transient transfection assays were performed as described before (Luscher-Firzlaff et al, 1999). Transformation assays using rat embryo cells were carried out essentially as described previously (Cerni et al, 1995).…”
Section: Cells Transient Transfections and Transformation Assaysmentioning
confidence: 99%
See 1 more Smart Citation